PENENTUAN JUMLAH GERHANA MATAHARI DENGAN ARGUMEN LINTANG BULAN DAN TEORI ARITMATIKA - Ehsan Hidayat (Institut Keislaman Abdullah Faqih Gresik, 2020)
Abstract: A solar eclipse is a natural phenomenon that occurs every year, albeit in different numbers. Territorially, eclipses can occur and be observed once or twice and globally, solar eclipses can occur in numbers of 2, 3, 4 or 5. These numbers inevitably form a separate pattern, both regular and irregular. However, in reality there is no literacy that explains the process of these numbers in detail. The algorithm for determining the timing of a solar eclipse is known for its complicated and tedious calculations. The number of paths that must be calculated makes the eclipse study less involved in the research. Arithmetic theory, which actually uses the concept of regularity of patterns from a sequence of numbers in practice, has not been used as part of the eclipse algorithm. Especially if it is related to the argument for the latitude of the moon (F) which is full of initial predictions of a solar eclipse. This article invites you to understand the number of solar eclipses through arguments for lunar latitude and arithmetic theory.Keyword: Solar Eclipse, Arithmetic, Lunar Latitude